Factors of violence: a study in Greek prisons = Faktoren der Gewalt: eine Studie in griechischen Gefängnissen - Lambropoulou, Efstathia (Kriminologie - das Online-Journal, 2023)
This article presents the main findings of a research study onthe development of violence in Greek prisons after 2009, considering prison density, prisoner/staff ratio (2015-2019) and prison size. The data cover interpersonal violence among inmates and against staff from the 34 prisons in Greece as recorded by the Ministry of Citizen Protection (General Secretariat of Crime Policy). In the first and second sec -tions, the article briefly presents the findings of existing studies onactors associated with prisoners’ misbehavior. The third section contains the empirical research. In the fourth section, some conclusions and remainingissues for further research as well as policy implications for Greek correctional institutions are discussed. This research confirms the results of several studies, i.e. that prison density, prisonsize and inmate/staff ratio as single factors are not enough to explain violence in prison.